PERANCANGAN CONTENT MANAGEMENT SYSTEM PROGRAM STUDI UNIVERSITAS DHYANA PURA MENGGUNAKAN METODE TCSD - Ni Putu Trisna Padmawati; Gerson Feoh; Putu Wida Gunawan (Jurnal Teknologi Informasi dan Komputer, 2017)
ABSTRACTDhyana Pura University is one of the Universities in Bali, which has 2 faculties andconsists of 14 courses. At Dhyana University Pura already has a website that is used to provideinformation to students and the general public. However, in every study program Dhyana PuraUniversity does not have standardization of Content Management System for study programinformation system. One of the steps that can be taken is to design the content management systemof study program to standardize every website of study program of Dhyana Pura University.Task Centered System Design method is a method in Human Computer Interaction (HCI)that is used to identify user needs and task needs. Where identification results are used as the basisof interface improvements supported by direct observation.Testing this system using Black Box method and it can be concluded that the contentmanagement system was successfully designed and implemented. So from the test results, thepurpose of making this system has been achieved where the user task needs have been inaccordance with the task and user type on the content management system of the study program ofDhyana Pura University.Keywords: Dhyana Pura University, Content Management System, Task Centered System Design,Black Boxes.ABSTRAKUniversitas Dhyana Pura adalah salah satu Universitas di Bali, yang mempunyai 2 fakultasdan terdiri dari 14 program studi. Di Universitas Dhyana Pura sudah mempunyai website yangdigunakan untuk memberikan informasi kepada mahasiswa dan masyarakat umum. Akan tetapi disetiap program studi Universitas Dhyana Pura belum memiliki standardisasi Content ManagementSystem untuk system informasi program studi. Salah satu langkah yang bisa ditempuh adalahdengan merancang content management system program studi untuk menstandardisasikan setiapwebsite program studi Universitas Dhyana Pura.Metode Task Centered System Design adalah sebuah metode dalam Human ComputerInteraction (HCI) yang digunakan untuk menegidentifikasikan kebutuhan user dan kebutuhantask. Dimana hasil identifikasi digunakan sebagai dasar perbaikan interface yang didukungdengan observasi langsung.Pengujian system ini menggunakan metode Black Box dan dapat disimpulkan bahwacontent management system ini berhasil dirancang dan diimplementasikan. Sehingga dari hasilpengujian, tujuan dari pembuatan system ini telah tercapai dimana kebutuhan task pengguna telahsesuai dengan task dan tipe pengguna pada content management system program studi UniversitasDhyana Pura.Kata kunci : Universitas Dhyana Pura, Content Managemen System, Task Centered SystemDesign, Black box